Electrospun ZnO–SnO2 Composite Nanofibers and Enhanced Sensing Properties to SF6 Decomposition Byproduct H2S - Lu, Zhaorui; Zhou, Qu; Wang, Caisheng; Wei, Zhijie; Xu, Lingna; Gui, Yingang (Frontiers in Chemistry, 2018)
Hydrogen sulfide (H2S) is an important decomposition component of sulfur hexafluoride (SF6), which has been extensively used in gas-insulated switchgear (GIS) power equipment as insulating and arc-quenching medium. In this work, electrospun ZnO-SnO2 composite nanofibers as a promising sensing material for SF6 decomposition component H2S were proposed and prepared. The crystal structure and morphology of the electrospun ZnO-SnO2 samples were investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM), respectively. The composition of the sensitive materials was analyzed by energy dispersive X-ray spectrometers (EDS) and X-ray photoelectron spectroscopy (XPS). Side heated sensors were fabricated with the electrospun ZnO-SnO2 nanofibers and the gas sensing behaviors to H2S gas were systematically investigated. The proposed ZnO–SnO2 composite nanofibers sensor showed lower optimal operating temperature, enhanced sensing response, quick response/recovery time and good long-term stability against H2S. The measured optimal operating temperature of the ZnO–SnO2 nanofibers sensor to 50 ppm H2S gas was about 250°C with a response of 66.23, which was 6 times larger than pure SnO2 nanofibers sensor. The detection limit of the fabricated ZnO–SnO2 nanofibers sensor toward H2S gas can be as low as 0.5 ppm. Finally, a plausible sensing mechanism for the proposed ZnO–SnO2 composite nanofibers sensor to H2S was also discussed.